Przemoc w wychowaniu… w polskim wydaniu. Postawy rodziców wobec kar cielesnych - Jarosz , Ewa (Studia Edukacyjne, 2018)
The worldwide discourse on the problem of corporal punishment presents the discussion and results of research that gives the evidence of serious harm that CP does. In this light the need of intensive efforts to eliminate corporal punishment as the most frequent form of violence against children is strongly emphasized in the last years. Among different activities dedicated to stop the problem research on various indicators correlated with the use of corporal punishment are recommended. One of them is social acceptance of violent behaviors in relationship with a child. Due to this recommendations also in Poland proper research has been done in order to get a diagnosis of social attitudes towards corporal punishment. This paper presents some results of the research of the year 2017 commissioned by the Ombudsman for Children, which was the 7th edition of the monitoring of social attitudes on violence in upbringing that has been continued since 2011. The below presentations focuses on results of parents as a group of the general population. Additionally parents were asked also about their own behaviors towards their children, as an attempt not to assess directly the range of the use of corporal punishment by them but to get the picture of the another face of their attitudes toward the problem. In the face of the results it can be said that the picture of parents’ approval of violence in upbringing must be regarded as problematic and needing determined interventions. The most problematic is the level of the acceptance of these behaviors, which often are not clearly named in a public space as violence like spanking. The level of the approval of violence toward children among Polish parents should be regarded as a negative context of child well-being in Poland which definitely conduces to the existence of violent behaviors in everyday rising practices and the harm experienced by children.